An Approach to Evaluate a Supply Chain Network - Khaled Mili (International Journal of Supply Chain Management, 2022)
Designing the supply chain network (SCN) is the first step to creating a chain sourcing for results. The process identifies the change that will differentiate an organization from its competitors, to contact a customer with a successful value proposition, reduce costs and boost profitability. The most effective way to ensure perfect fluidity is to appoint an employee responsible for supervising the entire process. The manager will inform and coordinate the activities of the heads of different departments, from shipping to sales, focusing on communication and identification of potential problems, as well as correcting faults before they lead to disruption. This paper proposes an evaluation approach for the supply chain network design problems under uncertainty. Existing approaches to this problem are either the deterministic environments or can only address a modest number of scenarios for the uncertain problem parameters. Our solution approach integrates both features; the collective evaluation and the selection of one.